Readiness and satisfaction of the online learning among medical students undergoing clinical rotation during covid-19 pandemic - Musa, Mohd Jamaluddin (2023)
Online learning has become an important teaching method across academic programs during COVID-19 pandemic. We examined students’ level of readiness and satisfaction on online learning and their association with selected variables. A cross-sectional study was conducted among medical students who undergo clinical rotation during restricted movement order, when face-to-face teaching and learning is converted into online method. Participants were recruited conveniently by inviting students from targeted clinical years to fill up Online Learning Readiness Scale (OLRS) and E-Course Satisfaction Scale (ECSS) distributed via digital platform. One-hundred and eighty-three (N=183) students in clinical posting of year 3 (33.9%), 4 (32.2%), and 5 (33.9%) completed the survey voluntarily. Majority was female (n=142, 78%) with a mean age of 22.85. Overall, they reported high level of readiness and satisfaction on online learning. There was positive moderate to good correlation between readiness and satisfaction (r=0.61, p < 0.001). Readiness was significantly associated with age (β = 1.12, p = 0.037), type of clinical posting (β = -4.09, p = 0.003), online attendance (β = 0.45, p = 0.008), and learning duration (β = 3.44, p = 0.036). Only duration of learning showed significant linear relationship with satisfaction. Medical students reported high levels of readiness and satisfaction on online learning, despite heavily relying on this online learning mode to complete their clinical posting, during COVID-19 pandemic.